2015
DOI: 10.1111/ics.12203
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the impact of urban pollution on the quality of skin: a multicentre study in Mexico

Abstract: The study demonstrated an important impact of polluted environmental conditions on skin quality, evidencing important modifications of superficial biochemical parameters. The cause/effects relationships of these modifications remain, however, to be further assessed by a complementary in vitro/in vivo approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
82
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 43 publications
8
82
2
1
Order By: Relevance
“…If and how this is indeed the case cannot be answered by the present study. It should be noted, however, that living in heavily polluted metropolitan areas was previously reported to be associated with increased production of sebum, which is a known pathogenic factor for acne vulgaris [8]. Also, biochemical analysis revealed qualitative changes in sebum in individuals living in polluted cities [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If and how this is indeed the case cannot be answered by the present study. It should be noted, however, that living in heavily polluted metropolitan areas was previously reported to be associated with increased production of sebum, which is a known pathogenic factor for acne vulgaris [8]. Also, biochemical analysis revealed qualitative changes in sebum in individuals living in polluted cities [8].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it is of interest that: (i) greasy skin was reported to be more frequent in individuals living in a Chinese metropolitan area as compared with a nonpolluted area [7], (ii) in subsequent studies sebum levels were indeed found to be increased in individuals living in major cities with high pollution levels [8], and (iii) the sebum of these individuals was qualitatively altered [8]. Overall, these studies indicate the possibility that air pollution may contribute to the aggravation of acne vulgaris.…”
Section: Introductionmentioning
confidence: 99%
“…After exposure to pollution, the skin is characterized with increased pH and lactic acid content. These are only a few examples which, if properly monitored, could be regarded as chemical markers to determine anti-pollution efficacy [14].…”
Section: Effect Of Pollutants On the Skin And Its Mechanism Of Actionmentioning
confidence: 99%
“…In vitro tests are based on the use of cell cultures or reconstituted skin models and evaluate several biomarkers (PGE2, IL-1α, MDA, superoxide dismutase, catalase, gluthathione reductase, to name just a few) after pollutants exposure [27,28]. In vivo tests, performed on volunteers' panels, include instrumental evaluation of skin parameters (such as skin hydration, transepidermal water loss or TEWL, skin elasticity, wrinkles, skin pigmentation) and the evaluation of the levels of oxidative stress and inflammatory markers after exposure to pollutant stressors [29,30]. The availability of reliable and specific markers of airborne pollution upon skin would allow to evaluate and quantify the cutaneous impact of this phenomenon, as well as to assess the effectiveness of ingredients or finished products in counteracting detrimental effects of air pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, an increase in soot (per 0.5 × 10 −5 per m) and particles from traffic (per 475 kg per year and square km) were associated with 20% more pigment spots on forehead and cheeks [29]. The influence of air pollutants on a number of skin parameters was evaluated in a clinical comparative study conducted on 96 subjects in Mexico City (one of the world's most polluted cities) and 93 subjects in Cuernavaca, considered a town preserved from urban pollution [30]. In this comparative study, the Authors studied quantitative and qualitative modifications of a number of skin parameters.…”
Section: Introductionmentioning
confidence: 99%